RP-HPLC Estimation of Isradipine in Pharmaceutical Dosage Forms - Gopal, Pasumarthy N.V.; Srinivas, V.D.N.; Padma, S.V.N. (Asian Journal of Chemistry, 2010)
A reverse phase high performance liquid chromatographic method has been developed for the estimation of isradipine in its capsule dosage forms using RP-C18 column. The mobile phase (methanol, acetonitrile and acetate buffer pH 2.8) was pumped at a flow rate of 1 mL/min in the ratio of 60:30:10 and the eluent were monitored at 290 nm. The intra- and inter-day variation was found to be less than 2 % showing high precision of the assay method when compared with reported result. The mean recovery of the drug from the solution containing 200 or 300 μg/mL was 99.66 ± 1.20 % indicating high precision and accuracy. The proposed HPLC method may be used for determining isradipine in bulk drug samples or in pharmaceutical dosage forms.